Teachers only stand behind parents and God in the eyes of Muslim pupils - Berglund, Jenny (2012)
In the course of reviewing a recent quantitative survey of approximately 1300 Swedish youths on subjects like religion and leisure activities, I came across a finding which seemed intriguing to me: some 50% of those identifying themselves as Muslims reported that they confided in their teachers (compared to only 5% of non-Muslims) for help with personal problems. Supplementing this finding with several studies as well as my own interviews, I explore its possible meanings and examine its implications relative to such matters as the value of relational skills in teaching, the content and direction of teacher training, the importance of the teacher-student relationship, and the potential of teachers to facilitate integration.
Keywords: Muslims; Sweden; Integration; relational skills; Teachers